Liberdade de expressão e desinformação em contextos eleitorais: parâmetros para enfrentamento com base nas sentenças da Corte interamericana de Direitos Humanos - GOLTZMAN, Elder Maia (2022)
This research seeks to investigate standards to deal with disinformation in electoral contexts from the judgments of the Inter-American Court of Human Rights that refer to freedom of expression. The objectives are to discuss freedom of expression, using as a theoretical background the contributions of John Stuart Mill; to understand disinformation and its implications, especially in electoral contexts; and to verify the content of freedom of expression in the interpretation of the Inter-American Court of Human Rights. The research techniques used are bibliographic and documentary, mainly the judgments from the Inter-American Court of Human Rights in cases that had freedom of expression as the merits of the dispute. The time lapse of the research was the last 20 years (2000-2020). The sustained hypothesis is that five standards must be observed to approach freedom of expression to deal with disinformation in electoral contexts, which are: the double dimension of freedom of expression, the honor of public officials and candidates is flexible, indirect means of intimidation curbing freedom of expression, criminalization of speeches and chilling effect, and the importance of press freedom for free speech. The inductive method was used. This research is categorized as legal descriptive, and it is in the field of legal dogmatics